If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2t = 29 + -7t Solving 4 + -2t = 29 + -7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '7t' to each side of the equation. 4 + -2t + 7t = 29 + -7t + 7t Combine like terms: -2t + 7t = 5t 4 + 5t = 29 + -7t + 7t Combine like terms: -7t + 7t = 0 4 + 5t = 29 + 0 4 + 5t = 29 Add '-4' to each side of the equation. 4 + -4 + 5t = 29 + -4 Combine like terms: 4 + -4 = 0 0 + 5t = 29 + -4 5t = 29 + -4 Combine like terms: 29 + -4 = 25 5t = 25 Divide each side by '5'. t = 5 Simplifying t = 5
| 6/4y-10=-4 | | 0=-.004x^2+12x-1500 | | 6s+5=15-4s | | (5r)(-2)=80 | | 9(c-4)=4+8c | | x^1/5∙x^1/6 | | 1/x(6x²) | | 6+5p=2p-21 | | x^(1/5)∙x^(1/6)= | | (x+5)2+3=(x-2)2 | | x^(1/5)∙x^(1/6) | | 48x^2-72x+324=0 | | 5-4r=9+2r | | 1/x(6xⁿ) | | -7+3x-4+2x= | | 7y=x+49 | | x^2+16x-7=4 | | 6(x+4)=x+2(x+11) | | 7n-8=2n+7 | | -5+-3x+-10x= | | x-10=.25+2 | | 6m+7=3m-2 | | 3x+10-x=7+x+1 | | 1y+2x=2 | | 8.4g=-15.6+4.4g | | x^2+16x+14=-1 | | 4+7p=3p | | -3(n+1)=-2n-4 | | y+y+-10x= | | -6x^4+48x^2-32=0 | | x^3+3x^2+9x= | | 4(x^2-5x+7)-8(x^2+4x-5)= |